An Ethnobotanical Study on Qīng-Căo-Chá Tea in Taiwan - Huang, Shyh-Shyun; Chen, Ting-Yang; Deng, Jeng-Shyan; Pao, Li-Heng; Cheng, Yung-Chi; Chao, Jung (Frontiers in Pharmacology, 2020)
Herbal tea, a beverage prepared from a variety of plant materials excluding the leaves of the tea plant Camellia sinensis, for a long time, has been consumed by most Chinese people for preventive and/or therapeutic health care. Usually, it is brewed or prepared as a decoction of local plants in water. The qīng-cǎo-chá tea, a commercial herbal tea, is the most common among many differently formulated herbal teas in Taiwan. For hundreds of years, qīng-cǎo-chá tea has played an important role in the prevention and treatment of diseases associated with the environmental conditions in Taiwan. However, research studies in this field have been insufficient. The raw material formulas of qīng-cǎo-chá tea have always been passed down from “masters” to “apprentices.” Hence, there is no systematic collation or record, and, therefore, there is a need to assess and confirm the composition, safety, and effectiveness of the raw materials. This study aimed to document the uses of Taiwan’s qīng-cǎo-chá tea through a semi-structured interview survey and investigate the background of traditional practitioners, tea compositions, and plant origins and uses. This will improve our understanding of the knowledge inherited by the practitioners and the theoretical basis of the medicinal uses of these teas. In our field investigation, we visited 86 shops and assessed 71 raw ingredients of qīng-cǎo-chá tea. A semi-structured questionnaire was used to conduct the interviews. During the interviews, in addition to written records, audio and video recordings were made, and photographs were taken with the permission of the interviewees. The qīng-cǎo-chá raw materials have long been used as herbal teas, although more research should clarify their efficacy and safety. Traditional sellers of qīng-cǎo-chá tea were mainly males, and most shops have been in operation for more than 71 years. Some of the raw materials were derived from multiple sources, including different plants, and were often mixed without any safety concerns. To our knowledge, this is the first systematic ethnobotanical study on qīng-cǎo-chá tea that assesses and confirms its herbal ingredients. Our study represents a reference for herbal teas in Taiwan that can be used by the public and regulatory agencies.